Behind the Curtain of Life of „Communist Elite“ - Starikovičius, Vytautas (Lietuvos istorijos studijos, 2017)
(about the thesis of Marius Ėmužis „Soviet Lithuania ruling elite 1944–1974: interpersonal relations and their expression“)